Pelatihan Komunikasi dan Instruksi Bahasa Inggris dan Bahasa Arab dalam Meningkatkan Kompetensi Guru - Akhyar, Yundri; Ningsih, Wirda; Zalisman, Zalisman; Khasanah, Niswatul; Hariati, Haryuni; Asmidaryani, Asmidaryani; Elmirawati, Elmirawati (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: The goal of community service is to improve the level of teacher competency in elementary schools by engaging in community service activities. The objective was to obtain this outcome by concentrating on communication and instructional development. Methodology: The Participatory Action Research (PAR) was chosen as the technique for this community service. Participatory Action Research (PAR) entails the active engagement of community members and relevant stakeholders with the objective of fostering collaborative problem-solving and knowledge acquisition. Results: The community service initiative enhanced the language and communication abilities of teachers. This implies that the training program has been successful in effectively addressing specific areas of teacher competency. Limitations: One obstacle to this training is related to the duration required for implementation. If the implementation time is short, it will produce less than the optimal results in the expected output. Contribution: The community service project implemented a notable enhancement in teacher proficiency in language and communication skills within the context of elementary education. This underscores the imperative for ongoing investment in teacher training to augment the calibration of education.